Influence of Attitude, Cooperative and Inquiry Instructional Strategies on the Academic Performance of Students in Basic Science and Mathematics in Katsina, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
Investigating the effects of cooperative learning as an instructional strategy for teaching basic science and mathematics to junior secondary school students in Katsina state was the focus of this study. Equally, it also looked at how gender affect students’ performance and attitude in basic science and mathematics when cooperative learning was used as an instructional strategy. Quasi-experimental design was used in the study with 240 students as sample selected purposively. Findings of the study revealed that students taught using cooperative learning strategy performed higher than those taught using inquiry learning strategy; there was an insignificant difference in performance between the male and female students in the cooperative learning group. The students in cooperative learning group show a more positive attitude towards basic science and mathematics than those in inquiry classroom learning. On the bases of these findings, it was recommended that cooperative learning strategy be adopted by all secondary school Basic Science and Mathematics teachers as an effective learning strategy in order to improve students’ performance and positive attitude towards science and mathematic